Pengaruh Rasio RDF MSW Dan Batubara Terhadap Nilai Net Plant Heat Rate (NPHR) Pada Co-Firing Insinerator Fluidized Bed - Winner, Michael Wor; Winaya, I Nyoman Suprapta; Astawa, Ketut; Pratama, I Putu Angga Yuda (Teknik Desain Mekanika, 2024)
Abstract The technology that is currently developing by utilizing waste as a mixed alternative fuel is direct co-firing technology. One of the emerging technologies is the fluidized bed incinerator utilizing Refuse Derived Fuel (RDF) as an alternative fuel. RDF is a fuel that is basically made from processed municipal waste with a high calorific value. The fuel mixing ratio has an effect on the performance of the fluidized bed incinerator, so this study focuses on variations in the ratio of RDF to coal by 5%, 10%, and 15%. Through the mass fraction conversion process, it was determined that the fuel mass requirement was 140 grams to fill the fuel volume inside the reactor. Thus, the 5% RDF percentage resulted in a mass ratio of 7 grams RDF and 133 grams coal, following the predetermined percentage of RDF MSW in this study. In this study, the incinerator temperature was kept stable at 850 OC with a controlled heater supply through the control panel and used a superficial velocity of 9m/s to maintain combustion quality. The results of this experimental study show that adding too much RDF to the fuel mixture will result in an increase in the NPHR value. As the value of NPHR increases, this indicates the performance of the incinerator decreases. This is shown by the 85% coal + 15% RDF variation, with the Net Plant Heat Rate (NPHR) value of 935.2 kcal/kWh, and burning time 940s. Keywords: Co-firing, RDF MSW, Fluidized Bed, Incinerator, NPHR